Pigmented cereals and legume grains as healthier alternatives for brewing beers. (April 2023) - Romano, Giuseppe; Tufariello, Maria; Calabriso, Nadia; Del Coco, Laura; Fanizzi, Francesco P.; Blanco, Antonio; Carluccio, Maria A.; Grieco, Francesco; Laddomada, Barbara
Abstract: Pioneering studies were carried out on red-to-black pigmented grains for brewing beers. Together with pigmented cereals, the use of pulses was also proposed for making low-alcohol, gluten-free beers with improved contents of health-promoting compounds. So far, a new concept of beer is emerging among scientists, brewers, and consumers by expanding the assortment of conventional beer's ingredients. Coloured (red, purple, blue, black) cereal grains and legume grains are an untapped resource of functional compounds. each denoting different and complementary beneficial effects on human health. Among others, polyphenols contribute to protect against non-communicable diseases such as hypertension, heart diseases, cancers, diabetes and obesity. In this review, we summarized the improvement in terms of phenolic compounds and antioxidant capacity of beers obtained by using pigmented cereal grains and pulses as raw ingredients versus traditional beers. We examined the influence of these alternative materials on the qualitative properties of the beers. Moreover, we reviewed the contribution of traditional and non-conventional yeasts on the flavour and quality of these new functional beers. Finally, we discussed the use of different and complementary chemical methods for monitoring the composition, organoleptic profile, safety, and authentication issues with the aim to highlight the most promising to protect and promote novel beer products. Highlights: New functional beers can be produced with pigmented cereals and pulses. Total phenolic and antioxidant properties enhanced in pigmented cereals beers. The use of 100% pigmented corn impact on the aromatic profile of beers. Pulses adjunct in beer brewing does not affect the sensorial quality of beers. Further studies are needed to test the effect of functional beers on human health.